Caracterización Anatómica de la Madera de Cinco Especies Comerciales del Sector la Colonia Simón Bolívar, Cantón Santa Clara, Provincia de Pastaza - Salinas, Bryan; Carpio, Carlos; Salazar, Eduardo; Noboa, Vilma; Espinoza, Manuel; Román, Daniel (European Scientific Journal, ESJ, 2019)
This paper proposes the anatomical characterization of the wood of five commercial species: Inga edulis Mart., Miconia rivalis Wurdack, Piptadenia flava (Spreng. ex DC.) Benth, Piptocoma discolor (Kunth) Pruski, and Syzyguium jambos (L.) Alston from Simon Bolivar Sector, Santa Clara Canton, and Pastaza Province. In order to perform this study, dendrologic and wood test tubes was taken from each species. To identify those species, some dendrologic samples in Escuela Superior Politecnica de Chimborazo´s herbal (CHEP) were collected. For the description of the macroscopic characteristics of the woods, they were previously dried for 30 days and were used for determining characteristics such as texture, luster, taste, odor, marbled wood, grain, and color. For the microscopic characteristics, cubes were obtained 2 cm per edge, softened in autoclave and with distilled water in different cycles depending on each species. Subsequently a microtome was used to make cuts of the different planes of the wooden cubes. These plates were placed in Petri dishes with different dyes (Bright green, Orcein (A and B)). The observation was made under the microscope and the pore types were determined in the three dyes, the size, and number of pores per species. La presente investigación propone la caracterización anatómica de la madera de cinco especies comerciales: Inga edulis Mart., Miconia rivalis Wurdack, Piptadenia flava (Spreng. ex DC.) Benth, Piptocoma discolor (Kunth) Pruski, Syzyguium jambos (L.) Alston, del Sector la colonia Simón Bolívar, cantón Santa Clara, provincia de Pastaza; para lo cual se tomaron muestras dendrológicas y probetas de madera de cada especie que fueron identificadas en el herbario de la Escuela Superior Politécnica de Chimborazo (CHEP). Para la descripción de las características macroscópicas de las maderas estas fueron previamente secadas durante 30 días y se utilizaron para la determinación de características como textura, lustre, sabor, olor, veteado, grano y color, mientras que para las características microscópicas se obtuvieron cubos de 2 cm por arista, ablandados en autoclave y con agua destilada en diferentes ciclos dependiendo de cada especie. Posteriormente se utilizó un micrótomo para realizar cortes de los distintos planos de los cubos de madera; estas láminas fueron colocadas en cajas Petri con los distintos tintes (Verde brillante, Orceína (A y B)). Se realizó la observación en el microscopio y se determinaron los tipos de poros en los tres tintes, el tamaño y número de poros por especie.